Trends in the diagnostic approach of scabies as a neglected tropical disease - `, Reqgi First Trasia (Explorer Front, 2020)
Scabies is a parasitic disease of the skin that is difficult to enforce if the clinical symptoms are not typical. The diagnosis relies on clinical symptoms to be less efficient and only has a sensitivity of less than 50% because it is difficult to distinguish active infestations, residual skin reactions, or reinfestations. Misdiagnosis results in wrong treatment and causes the patient to not recover and continues to be a source of infection for the environment. The exact diagnosis of scabies is determined by finding mites or eggs on laboratory tests, but mites are difficult to find because only a few mites infest sufferers. For this reason, various studies in the world have tried to develop diagnostic methods in the enforcement of scabies. This article will describe the trend of establishing a diagnosis of scabies, as well as the advantages and disadvantages in its application.